Keberpihakan Sistem Peradilan dalam Upaya Perlindungan Kebebasan Akademis Kampus dalam Berkumpul dan Berserikat (Studi Analisis Putusan Nomor 23 /Pid.Sus/2015/PN Kln) - Holish, Amarru Muftie (Fakultas Hukum Universitas Negeri Semarang, 2020)
Academic freedom is one of the breaths of academic citivas in raising the facts of empirical facts of science. This fact of fakat should be addressed in scientific studies as a form of academic discipline. guaranteeing academic freedom is the basic and fundamental thing to be explored and absorbed, the role of the judicial institution as a display of academic freedom protection is a definite and sharp benchmark for the state and law's alignment through its decisions we can explore the alignments and extent of the protection of academic freedom in Indonesia. in this study the author tries to take one of the court's decisions that the authors intend to practice legal protection to find out how often the state is concerned with the issue of academic freedom. n there are more advanced and rigorous research that examines the justice system's partiality in upholding academic freedom to create quality academic products